Regular soldiers, irregular war : violence and restraint in the second intifada - Manekin, Devorah S. (Cornell University Press, 2020)
"Starting from the observation that soldier participation in violence varies, this book looks into the dynamics of small military units to show how shifting modes of military control shape patterns of participation in violence in counterinsurgency"--